2022
DOI: 10.1007/s12671-022-01858-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness-Based Stress Reduction on Trauma in Victims of Gun Violence: a Pilot Study

Abstract: Objectives Gun violence is a significant problem in the United States of America. Gun violence produces lifelong psychological adversity, trauma, and grief. In the face of this epidemic, efficacious therapies that assuage gun violence-based trauma and negative health are lacking. Methods The proposed, longitudinal pilot experiment examined the effects of an 8-week mindfulness-based stress reduction (MBSR) program on traumatized individuals as a direct cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…We observed a trend for improvement in SBP at the 3-month follow-up in the MBSR group, with decreased DBP and MABP at 1 month and 3 months post-intervention. These findings align with studies demonstrating the potential of in lowering BP in clinical populations such as cancer and hypertension [ 24 , 25 ] as well as non-clinical populations like healthcare workers and victims of gun violence [ 26 , 27 ]. Additionally, a previous study found sustained decreases in cholesterol levels after MBSR in older adults at risk for coronary artery disease [ 28 ], and which may further impact blood pressure regulation [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…We observed a trend for improvement in SBP at the 3-month follow-up in the MBSR group, with decreased DBP and MABP at 1 month and 3 months post-intervention. These findings align with studies demonstrating the potential of in lowering BP in clinical populations such as cancer and hypertension [ 24 , 25 ] as well as non-clinical populations like healthcare workers and victims of gun violence [ 26 , 27 ]. Additionally, a previous study found sustained decreases in cholesterol levels after MBSR in older adults at risk for coronary artery disease [ 28 ], and which may further impact blood pressure regulation [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Reduce media consumption. Using techniques to relieve stress by breathing in and out, mindfulness, and exercising related to the regular events of "grief" issue tags showed a signi cant increase in proportion in the week following the shooting [30]. In contrast, there is extant existing knowledge demonstrating that public mass shooting attacks produce a high occurrence of posttraumatic stress and depression that leads to suicidal ideas and showed a signi cant decrease in proportions the week following the shooting [18,28,31,32].…”
Section: Discussionmentioning
confidence: 99%